2019
DOI: 10.1080/23802359.2019.1666669
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome sequence of Docynia indica (Wall.) Decne

Abstract: Docynia indica (Wall.) Decne. (Duo-Yi) is a high economic value for exploitation and utilization wild fruit tree species with edible and medicinal values in southwest China. We have sequenced the chloroplast genome to facilitate genetic improvement of this species and to assess phylogenetic relationships among major lineages. The result showed that the total chloroplast genome size of Duo-Yi was 159,546 bp in length, containing a pair of inverted repeats (IRs) of 26,369 bp, which were separated by a large sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Until now, there have been no genomic studies of O. boluoensis and the complete genomic sequence of its chloroplast (cp) has not previously been reported. Complete cp genomes are useful tools that provide information regarding phylogenetic relationships, species identification and germplasm diversity (Wang et al 2019). Therefore, in this study, we reported the complete genomic sequence of the cp from O. boluoensis using high-throughput sequencing approaches.…”
Section: Chloroplast Genome; Ormosia Boluoensis; Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, there have been no genomic studies of O. boluoensis and the complete genomic sequence of its chloroplast (cp) has not previously been reported. Complete cp genomes are useful tools that provide information regarding phylogenetic relationships, species identification and germplasm diversity (Wang et al 2019). Therefore, in this study, we reported the complete genomic sequence of the cp from O. boluoensis using high-throughput sequencing approaches.…”
Section: Chloroplast Genome; Ormosia Boluoensis; Phylogenetic Analysismentioning
confidence: 99%
“…Complete cp genomes are useful tools that provide information regarding phylogenetic relationships, species identification and germplasm diversity (Wang et al. 2019 ). Therefore, in this study, we reported the complete genomic sequence of the cp from O. boluoensis using high-throughput sequencing approaches.…”
mentioning
confidence: 99%
“…In this study, we present a new assembly of the complete chloroplast genome of Sorbus aucuparia L., another representative of Sorbus s.s. Given the availability of complete chloroplast genomes of several Maleae species assembled recently by various research groups [8,[13][14][15][16][17][18], we attempted to reconstruct the phylogeny of the Maleae tribe based on complete chloroplast genomes, with a special focus on the relationships among the genera formerly assigned to Sorbus s.l.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies were focused on its quality standard, chemical composition, and pharmacological activities (Wei et al 2012;Jiang et al 2013). It is well known that the chloroplast (cp) genomes have been widely applied to molecular identification and phylogenetic evolution of plant species (Wang et al 2019). However, up to now, no cp genome of F. tikoua has been reported in NCBI and other databases.…”
Section: Ficus Tikoua Bur; Complete Chloroplast Genome; Phylogenetic Analysismentioning
confidence: 99%